Modifier Genes and their effect on Duchenne Muscular Dystrophy - Vo, Andy H. (Curr Opin Neurol, 2015)
PURPOSE OF REVIEW: Recently, genetic pathways that modify the clinical severity of Duchenne Muscular Dystrophy have been identified. The pathways uncovered as modifiers are useful to predict prognosis and also elucidate molecular signatures that can be manipulated therapeutically. RECENT FINDINGS: Modifiers have been identified using combinations of transcriptome and genome profiling. Osteopontin, encoded by the SPP1 gene, was found using gene expression profiling. LTBP4, encoding latent transforming growth factor β binding protein 4 was initially discovered using a genomewide screen in mice and then validated in cohorts of Duchenne Muscular Dystrophy patients. These two pathways converge in that they both regulate TGFβ. A third modifier, Anxa6 that specifies annexin A6, is a calcium binding protein has been identified using mouse models, and regulates the injury pathway and sarcolemmal resealing. SUMMARY: Genetic modifiers can serve as biomarkers for outcomes in Duchenne Muscular Dystrophy. Modifiers can alter strength and ambulation in muscular dystrophy, and these same features can be used as endpoints used in clinical trials. Moreover, because genetic modifiers can influence outcomes, these genetic markers should be considered when stratifying results in muscular dystrophy.